An Extended Path Following Algorithm for Graph-Matching Problem - Liu, Zhi-Yong; Qiao, Hong; Xu, Lei (IEEE transactions on pattern analysis and machine intelligence, 2012)
The path following algorithm was proposed recently to approximately solve the matching problems on undirected graph models and exhibited a state-of-the-art performance on matching accuracy. In this paper, we extend the path following algorithm to the matching problems on directed graph models by proposing a concave relaxation for the problem. Based on the concave and convex relaxations, a series of objective functions are constructed, and the Frank-Wolfe algorithm is then utilized to minimize them. Several experiments on synthetic and real data witness the validity of the extended path following algorithm.